Montessori preschool 4 years - Ismail, Nik Ahmad Hisham (IIUM Educare Sdn. Bhd., 2013)
EDUCARE SERIES comprise of effective and interesting workbooks based on the National Preschool Curriculum of the Ministry of Education, Malaysia. The curiosity and learning of knowledge, skills and values. Educare Series thereby are not only a foundation for learning but "a fountain of learning" for all young children